KARAKTERISTIK BIOPELET DARI VARIASI BAHAN BAKU SEBAGAI BAHAN BAKAR ALTERNATIF - Zikri, Ahmad (KINETIKA, 2018)
The national petroleum reserves in form as proven reserves or potential reserves continue to decrease every year. The decreace of potential fossil energy encourages goverment to prioritize renewable energy to avoid energy crisis, one of them which is biomass pellet (biopellet). Biopellet is a fuel which made from densified solid biomass. The purpose of this study was to know the effect of mixed material and the best composition of biopelet made from coconut fiber and damar latex and the quality compared with the existing quality standard. In this research, there are two form of biopelet,which is biopelet from saw dust and kenanga, and the other is biopellet from coconut fiber and damar latex. The ratio of saw dust and kenanga in first form is 5:1 and 10:1 which is seperate by variation of its size 20, 60, and 170 mesh. And the second form with damar latex composition is 0%, 10% and 20% with the size of coconut fiber + 60 mesh. The mixture is molded into biopelet and then tested to determine the value of heat, density, moisture content, ash content, volatile matter content and fixed carbon. From the result of research, it is found that the best biopellet composition of the first form is the sample with the ratio of saw dust and kenanga 5:1 in size 20 mesh that produces biopellet with moisture content of 2.8846%, ash content of 3.8835%, volatile matter content 70.1402%, fixed carbon 23.0917%, density 0.8114 gr/cm3 , and calorific value of 4724.0509 cal/gram. And for the second form the best biopellet is with composition coconut fiber 80% and damar latex 20%, that produces moisture content of 3.2872%, ash content of 2.4866%, volatile matter content 77.7634%, fixed carbon 16.4628%, density 1.4363 gr/cm3 , initial flame up to fire 8.10 seconds and calorific value of 5243.7426 cal/gram. Calorific value, physical analysis and chemical analysis of this biopelet meet the standards of SNI 8021-2014.